(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
By substituting 1-(4-Nitrobenzyl)-5-imidazolyl or 2-methylthio-1-(4-Nitrobenzyl)-5-imidazolyl for the orthonitrophenyl group on location 4, new analogues of nifedipine, an established calcium channel blocker, were synthesised. In male rats, the effects of the newly synthesised compounds on blood pressure were analysed using an indirect tail-cuff procedure at 15, 30, and 60 minutes after administration and compared to nifedipine.